Thrombopoietin Receptor Agonists in Patients with Chronic Liver Disease - Khemichian, Saro; Terrault, Norah A. (Seminars in Thrombosis and Hemostasis, 2020)
Thrombocytopenia is one of the most common hematologic complications in cirrhosis. Despite limited data linking platelet count and bleeding risk in patients with cirrhosis, the use of platelets transfusions for invasive procedures has been a common practice. Recently, thrombopoietin (TPO) receptor agonists have been approved for use in patients with chronic liver disease (CLD) undergoing invasive procedures. The aim of this study was to review current literature on bleeding risk in patients with cirrhosis and the use of platelet transfusions and TPO receptor agonists in the context of invasive procedures. PubMed search was conducted to find articles relating to cirrhosis, thrombocytopenia, and new novel treatments for this condition. Search terms included CLD, cirrhosis, thrombocytopenia, bleeding, thrombosis, coagulopathy, hemostasis, and TPO receptor agonists. Romiplostim, eltrombopag, avatrombopag, and lusutrombopag are approved TPO receptor agonists, with avatrombopag and lusutrombopag specifically approved for use in patients with CLD undergoing invasive procedures. In patients with platelet counts < 50,000/mm3, avatrombopag and lusutrombopag increased the platelet counts above this threshold in the majority of treated patients and reduced the frequency of platelet transfusions. At the approved doses, incidence of thrombosis was not increased and therapies were well tolerated. Studies were not powered to assess whether risk of bleeding complications was reduced and the fundamental question of whether correction of thrombocytopenia is warranted in patients undergoing invasive procedures remains unanswered. The use of TPO receptor agonists has resulted in less requirement for platelet transfusions. In patients with cirrhosis undergoing invasive procedures for whom platelet transfusion is planned, TPO receptor agonists are an alternative and avoid the risks associated with transfusions. However, there is need for a thoughtful approach to manage bleeding risk in patients with cirrhosis undergoing procedures, with the consideration of a comprehensive hemostatic profile, the severity of portal hypertension, and the complexity of the invasive procedure to guide decisions regarding transfusions or use of TPO receptor agonists.
Keywords: cirrhosis; avatrombopag; lusutrombopag; hemostasis; bleeding; thromboelastography; portal vein thrombosis